Void space inside the developing seed of Brassica napus and the modelling of its function. Issue 4 (21st May 2013) - Verboven, Pieter; Herremans, Els; Borisjuk, Ljudmilla; Helfen, Lukas; Ho, Quang Tri; Tschiersch, Henning; Fuchs, Johannes; Nicolaï, Bart M.; Rolletschek, Hardy
Summary: The developing seed essentially relies on external oxygen to fuel aerobic respiration, but it is currently unknown how oxygen diffuses into and within the seed, which structural pathways are used and what finally limits gas exchange. By applying synchrotron X‐ray computed tomography to developing oilseed rape seeds we uncovered void spaces, and analysed their three‐dimensional assembly. Both the testa and the hypocotyl are well endowed with void space, but in the cotyledons, spaces were small and poorly inter‐connected. In silico modelling revealed a three orders of magnitude range in oxygen diffusivity from tissue to tissue, and identified major barriers to gas exchange. The oxygen pool stored in the voids is consumed about once per minute. The function of the void space was related to the tissue‐specific distribution of storage oils, storage protein and starch, as well as oxygen, water, sugars, amino acids and the level of respiratory activity, analysed using a combination of magnetic resonance imaging, specific oxygen sensors, laser micro‐dissection, biochemical and histological methods. We conclude that the size and inter‐connectivity of void spaces are major determinants of gas exchange potential, and locally affect the respiratory activity of a developing seed. Abstract : See also the Commentary by Macherel.